Māori university graduates: indigenous participation in higher education. Issue 3 (3rd May 2016) - Theodore, Reremoana; Tustin, Karen; Kiro, Cynthia; Gollop, Megan; Taumoepeau, Mele; Taylor, Nicola; Chee, Kaa-Sandra; Hunter, Jackie; Poulton, Richie
ABSTRACT: Māori, the indigenous population of New Zealand, are gaining university qualifications in greater numbers. This article describes the history of Māori university graduates, their current situation and the implications for indigenous futures. Section one provides a brief overview of historical policies and practices that, similar to those used on other indigenous populations, resulted in the widespread exclusion of Māori from university education until the 1970s and 1980s. Section two describes findings for Māori university graduates ( n = 626) from the Graduate Longitudinal Study New Zealand (GLSNZ). Results show that nearly half (48.4%) were the first member of their immediate family to attend university. Humanities/education (50.8%) was the most common domain of study followed by commerce (17.7%), science/engineering (15.4%), health sciences (10.9%), law (2.8%) and PhD study (2.4%). More Māori graduates were females (71%). One-third of graduates were parents, and being a parent was associated with a lower likelihood of studying science and engineering compared to those participants without children. The most common areas/fields that participants wished to work in post-graduation were education and training (28.3%), health care and medical (17.4%) and government (11.8%). Despite increases in higher education participation and completion, parity remains an issue. Similar to previous indigenous research findings, Māori are under-represented as graduates (7.1% of the total sample) and in particular as postgraduates (5.8%) considering that Māori constitute 14.9% of the New Zealand population. Contemporary indigenous graduates are critical for indigenous development. Over the next 10 years, the GLSNZ will follow graduates and provide insights into Māori graduate outcomes.